Analisis Isu Kontroversial Konflik Palestina-Israel pada Podcast Deddy Corbuzier Bersama Buya Arazy - Asmaunizar Asmaunizar; Hasrat Efendi Samosir Hasrat Efendi Samosir; Katimin Katimin; Nurul Fajri Nurul Fajri (Lembaga Sepercenter, 2024)
This research is entitled Analysis of Controversial Issues of the Palestinian-Israeli Conflict on the Deddy Corbuzier Podcast with Buya Arazy (Ferdinand de Saussure Semiotics Analysis). The purpose of this research is to find out how the controversial issues that Buya Arazy views on the Palestinian-Israeli Conflict through a podcast on Deddy Corbuzier's Youtube channel entitled Behind the Palestinian Genocide, There is an Invisible Mastermind, Israel and ....’. This research uses Ferdinand de Saussure's Semiotics Analysis model which divides the sign into two, namely signifier and signified. then the results of the study were found including: Not pro Hamas and Fatah, the Palestinian State has an internal conflict that is the cause of their war and many bad people take advantage of the donations of the Indonesian people.